Bio-inspired chameleon technique in mac protocol for energy efficient wireless sensor networks - Yousif, Alaa Kamal (School of Computer and Communication Engineering, 2018)
This thesis focuses on the development and integration of an enhanced Chameleon Mechanism (CM) for improving the efficiency of B-MAC protocol in partial of farm1 (PF1), partial of farm2 (PF2), and hybrid WSN scenarios. The development of CM involves the use of TM and DEA. Both optimization methods are integrated with B-MAC based-on INET3.5 simulation framework and OMNET++ simulator.